Extending coverage under the Argentinian pension system: Distribution of access and prospects for universal coverage - Arza, Camila (2012)
One of the main challenges facing social policy in Latin American is to guarantee social security coverage for the entire population in the presence of a large informal sector. In Argentina, a regional pioneer in terms of the development of its pension system, more than one third of those of retirement age were without benefits in 2005. Since then, considerable progress has been made in extending coverage thanks to the introduction of a programme that has reduced contribution requirements and allocated benefits to a large number of seniors previously excluded from the system. This article analyzes the impact of this process in Argentina on the level and distribution of coverage, identifies changes in socio-demographic factors which affect inclusion/exclusion in the social security system, and discusses remaining obstacles to the provision of universal coverage in the medium and long term.